Pengaruh Pemberian Edukasi Gizi pada Kejadian Anemia terhadap Tingkat Pengetahuan dan Sikap Remaja - Anisah, Anisah; Fajriani, Laksmi Nur; Isasih, Widani Darma (Puslitbang Sekawan Institute Nusa Tenggara, 2024)
(1) Anemia is a condition characterized by a lower than normal count of red blood cells (hemoglobin) for specific age and gender groups. Among teenagers, it is often caused by insufficient consumption of iron-rich foods, underscoring the importance of establishing healthy eating habits with adequate nutrients. Adolescent girls are particularly at risk for anemia, largely due to a lack of awareness about iron-rich foods and the crucial role of iron in their health. To prevent this, improving teenagers' knowledge through nutrition education via various media is essential. This research aims to evaluate the effect of nutrition education on adolescents' understanding of anemia.; (2) Methods: This study uses a literature review method, collecting data from various sources on the topic.; (3) Results: A review of ten studies indicates that nutrition education positively impacts adolescent girls' knowledge of anemia.; (4) Conclusions: Increasing knowledge through nutrition education using educational media is an effective strategy to prevent anemia in Indonesian adolescents.